Test usability guidelines and follow conventions. Useful recommendations from web developers - Alonso-Virgós, Lucía; Thomaschewski, Jörg; Pascual Espada, Jordán; González-Crespo, Rubén (Computer Standards and Interfaces, 2020)
Usability measures the quality of use when a user interacts with a website. There are many guidelines and recommendations to improve the user experience on websites. The purpose of this study is to analyze the degree of compliance with the well-known recommendation “follow conventions.” The behavior of 20 IT engineers is analyzed to obtain application data for each of the associated guidelines. This test is carried out with web developers without training in web usability. The purpose of the analysis is to know if there are guidelines that are applied innate. As web developers are also users, it is thought that there may be some innate behavior when applying these guidelines. The purposes of the paper are: (1) Make a list of the most forgotten recommendations by web developers to think about the importance of offering specific training in this field. (2) Know the most important recommendations according to web developers. To get the study purposes the research is carried out as follows. User tests are carried out to evaluate the most forgotten and applied proposals by the developers. Examinations are also done to determine the level of compliance since the participants lack experience in web usability. Interviews with web developers are carried out to evaluate the recommendations considered necessary. It is expected to find results that help to understand if a web developer without training in usability can innately apply guidelines on conventions. And if this native application of the guidance it is useful. We want to show that there are guidelines that are used intuitively. And that there are guidelines that do not apply, and the reason for each situation. The results indicate that the guidelines considered essential and those most applied by web developers without training have something in common. All of them focus on design and seek to design and adjust to known standards that facilitate user navigation.
Keywords: conventions; guidelines; recommendations; web usability; Scopus; JCR